Responsive Skin Application Techniques in Energy-Efficient Buildings - Alagöz Konur, Meryem; Türker, Sevim Gülen; Sarıcıoğlu, Pelin (The Indonesian Institute of Science and Technology Research, 2024)
Energy efficient buildings are those that consume less energy with the measures taken during the design process, meet the energy they need from renewable sources, and make a minimum environmental impact by using the energy obtained most effectively. Within the scope of this study, energy-efficient buildings were selected because they emphasize environmental sensitivity in the design, construction, and use phases. The study aims to analyze the sensitive volumes through algorithmic graphic programs and categorize them according to the application technique. The study is based on written sources, internet databases, and photographs. Visuals and examples are used to give details. In energy-efficient building design, responsive skin algorithmic application techniques provide optimum energy in a short time and make a great contribution to the national economy.